2014
DOI: 10.1177/0748233714532996
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthin inhibits CCl4-mediated oxidative stress and hepatic fibrosis by down-regulating TNF-α/NF-κB, and pro-fibrotic factor TGF-β1 mediating inflammatory signaling

Abstract: Hepatic fibrosis is an important outcome of chronic liver injury and results in excess synthesis and accumulation of extracellular matrix (ECM) components. Phyllanthin (PLN) isolated from Phyllanthus amarus exhibits strong antioxidative property and protects HepG2 cells from carbon tetrachloride (CCl4)-induced experimental toxicity. The present study reports the antifibrotic potential of PLN. The in vivo inhibitory effect of PLN on CCl4-mediated lipid peroxidation and important profibrotic mediator transformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Earlier findings have stated the antiapoptotic and anti‐inflammatory role of phyllanthin and hypophyllanthin in colitis‐induced Wistar rats (Kandhare et al, ). Another study has reported the ability of phyllanthin to suppress the oxidative stress as well as hepatic fibrosis in CCl 4 ‐induced mice by downregulating inflammatory cytokines production and NF‐κB activation (Krithika, Jyothilakshmi, & Verma, ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier findings have stated the antiapoptotic and anti‐inflammatory role of phyllanthin and hypophyllanthin in colitis‐induced Wistar rats (Kandhare et al, ). Another study has reported the ability of phyllanthin to suppress the oxidative stress as well as hepatic fibrosis in CCl 4 ‐induced mice by downregulating inflammatory cytokines production and NF‐κB activation (Krithika, Jyothilakshmi, & Verma, ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a P. amarus extract decreased DNA fragmentation in acetic acid-induced colitis in rats [11]. In addition, there is some evidence that phyllanthin inhibited TNF-α expression and prevented activation of the nuclear factor-κB in hepatic tissue [32]. Thus, the finding in this study clearly support the antiapoptotic role of phyllanthin, the mechanism of which was to ameliorate the disturbances caused by oxidative stress and loss of mitochondrial function, with inhibition of the subsequent apoptosis cascade.…”
Section: Discussionmentioning
confidence: 98%
“…[1,2] This lignan has demonstrated a broad spectrum of pharmacological activities such as hepatoprotective, antioxidative, antihyperuricemic and antibacterial. [3][4][5][6] Daily supplementation of phyllanthin for 3 months to mice fed with high fat diet was also able to lower serum triglycerides and free fatty acids, and, therefore, might be able to protect against metabolic disorders. [7] When a compound is taken orally, several events can occur during its absorption process including drug interaction.…”
Section: Introductionmentioning
confidence: 99%